The regeneration of military brownfields in Serbia: Moving towards deliberative planning practice?. (March 2021) - Peric, Ana; Miljus, Milutin
Highlights: Brownfield regeneration demands deliberation between various stakeholders. Deliberative practice complies to both reflective and collaborative planning. Neutral moderator secures open and fair communication. Public deliberation serves as an effective tool for solving complex problems. Abstract: This paper investigates the regeneration process of military brownfields in Serbia through the lens of a deliberative planning approach. The topic is important for Serbia as a proto-democratic society where brownfield regeneration follows market rules, thus neglecting the interests of other actors. However, military brownfields are considered an exception in this regard as the starting point for their revitalisation is agreement between public institutions – the Ministry of Defence and municipalities. This, however, does not mean that the regeneration process runs smoothly. Considering this issue from the perspective of theory, the paper examines the starting assumptions of deliberative planning to highlight the role of the moderator in the public deliberation procedure. An empirical in-depth case study illustrates the regeneration of the Army Club in Vršac, Serbia, based on collaboration among various national bodies (ministries), local authorities, local entrepreneurs, and other agencies that facilitate the process. Using analysis of the institutional framework, findings of desk research, and interviews with key informants, the paper contributes to an understanding of the limits and potentials of deliberative practice for regeneration of military brownfields. More importantly, it outlines a theoretically informed and empirically tested mechanism to tackle the critical issues, elements, and steps discovered by an exploration of the process. The lessons prove valid not only for Serbia, but also for similar socio-spatial contexts.